UNSGER METTANG (Motion Element of Capture Method): Development of Two-Handed Capture of Pencak Silat - Titin Andri Aningsih; Satrio Sakti Rumpoko; Rima Febrianti (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
The two-handed catch method is currently needed in training as part of the slamming or dropping technique, because of this this study aims to develop a two-handed catch training method in pencak silat based on indicators of comfort, effectiveness, convenience, accuracy, and feasibility as a source of student practice. PRSH Boyolali. The approach used in this research is R&D (Research & Development). The data obtained in this study were processed using quantitative and qualitative data analysis techniques (mix method). Based on data analysis in this study, the results for convenience were 4.5883 and 17.6, indicators for effectiveness were 4.2667 and 22.25, indicators for convenience were 4.3333 and 13.8, indicators for accuracy were 4.8889 and 26.85 , and feasibility indicators of 4.6667 and 9.15. The total indicator seen from the results of experts and students obtained an average value of 4.5477 and 4.4825. Based on the results of these average scores, a score in the "Very Good" category is obtained and is suitable for use in training as a two-handed catch exercise at PRSH Boyolali. The limitation in developing the two-handed catch training method in pancake silat include the time that cannot be determined, so that in the process it tends to follow the abilities of the students. This research is expected to make it easier for trainers to carry out the training process and to know the students’ process in doing two-handed catches, so that it is useful for students, trainers, as well as for training. With the limitations and contributions of these studies, further research is needed to optimize this research in the future regarding improving students’ abilities using the two-handed catch method.